2002
DOI: 10.1021/jf011107o
|View full text |Cite
|
Sign up to set email alerts
|

3-Deoxypentosulose:  An α-Dicarbonyl Compound Predominating in Nonenzymatic Browning of Oligosaccharides in Aqueous Solution

Abstract: The thermal degradation of D-glucose, maltose, and maltotriose in aqueous solution was investigated under caramelization (no glycine) and Maillard (with glycine) conditions. Degradation of the sugar and alpha-dicarbonyls product was monitored. Under both caramelization and Maillard reaction conditions, 3-deoxypentosulose was the predominating alpha-dicarbonyl compound formed from maltose and maltotriose. In the absence of an amino compound, however, 3-deoxypentosulose is formed in much lower concentration. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 13 publications
1
48
0
Order By: Relevance
“…In these foods, the precursor 3-deoxypentosone can form during degradation reactions of starch and oligosaccharides, especially in the presence of water [31,32]. Under quasi water-free conditions, 1,4-dideoxyhexosulose is cleaved from oligosaccharides and possibly starch in the presence of amines [31].…”
Section: Measurement Of Formyline and Pyrraline In Food Samplesmentioning
confidence: 99%
“…In these foods, the precursor 3-deoxypentosone can form during degradation reactions of starch and oligosaccharides, especially in the presence of water [31,32]. Under quasi water-free conditions, 1,4-dideoxyhexosulose is cleaved from oligosaccharides and possibly starch in the presence of amines [31].…”
Section: Measurement Of Formyline and Pyrraline In Food Samplesmentioning
confidence: 99%
“…AA formation is favoured as a consequence of the lower reactivity of sucrose and the already high presence of monosaccharides in breakfast cereals, mainly from thermal and Maillard-mediated hydrolysis of disaccharides. 21 Statistically significant differences in the FA content were found between cereals based on wheat and corn flours and those based on rice or the mixed cereals (Table 5).…”
Section: Resultsmentioning
confidence: 97%
“…The present results showed that the pathway involving 3-deoxypentulose might be one of the main routes for maltose degradation at pH 7-8. Hollnagel and Kroh (2002) reported that 3-deoxypentosulose is the predominant ␣-dicarbonyl compound specifically formed from 1,4-linked oligosaccharides, i.e. maltose and maltotriose, under both caramelization and Maillard reaction conditions.…”
Section: Resultsmentioning
confidence: 99%